Second language learning of depiction in a different modality: The case of sign language acquisition - Kurz, Kim B.; Kartheiser, Geo; Hauser, Peter C. (Frontiers in Communication, 2023)
This study investigated the acquisition of depicting signs (DS) among students learning a signed language as their second-modality and second-language (M2L2) language. Depicting signs, broadly described, illustrate actions and states. This study sample includes 114 M2L2 students who were recruited from college-level American Sign Language (ASL) courses who watched and described three short clips from Canary Row the best they could in ASL. Four types of DS were coded in the students’ videorecorded retellings: (1) entity depicting signs (EDS); (2) body part depicting signs (BPDS); (3) handling depicting signs (HDS); and (4) size-and-shape specifiers (SASS). Results revealed that SASS and HDS increase in instances as students advance in their ASL learning and comprehension. However, EDS expressions did not have a relationship with their ASL comprehension. ASL 2 students produced less DS than the ASL 1 students but did not differ from the ASL 3+ students. There were no differences in instances of BPDS among the three groups of L2 learners although their ability to produce BPDS was correlated with their ASL comprehension. This study is the first to systematically elicit depicting signs from M2L2 learners in a narrative context. The results have important implications for the field of sign language pedagogy and instruction. Future research, particularly cross-sectional and/or longitudinal studies, is needed to explore the trajectory of the acquisition of DS and identify evidence-based pedagogical approaches for teaching depicting signs to M2L2 students.